PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERBASIS PROBLEM BASED LEARNING UNTUK MEMFASILITASI KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA - Annisa Fadila Qinvi; Aty Nurdiana; Elvandri Yogi Pratama (Epsilon: Jurnal Pendidikan Matematika, 2023)
The background to this research and development of student worksheet is mathematics teaching material for 8th class of Junior High School 33 Bandar Lampung which have not fully facilitated the ability to solve mathematical problem. In this study it was found that the teaching materials used did not fully support the problem-solving abilities of each learning material through scientific activities. The type of research used is Research and Development (R&D) with the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) model. The results of the LKPD validation for media experts obtained a value of 4.69, material validation obtained a value of 4.90 and language validation obtained a value of 4.24, all of which are "Valid" criteria. After using LKPD based on developed Problem Based Learning, learning completeness through tests of students on the ability to solve mathematical problems reached classical completeness of 84,4%. These results state that LKPD based on Problem Based Learning of 8th class of Junior High School is appropriate for use as teaching materials.